Urban junco flight initiation distances correlate with approach velocities of anthropogenic sounds. Issue 2 (4th March 2023) - Lukas, Kara; Stansell, Hayley M.; Yeh, Pamela J.; Nonacs, Peter
Abstract : Urban-dwelling birds face novel visual cues and soundscapes. To thrive in these challenging environments, individuals must correctly identify and calibrate threats posed by humans and their activities. We showed that Dark-eyed juncos ( Junco hyemalis ) residing in an urban habitat responded differently to the sounds that approaching people and objects make. A person approached juncos simultaneously playing the sounds of object types that normally move at different relative velocities: faster (bicycles), intermediate (skateboards and scooters), or slower (people walking). Juncos responded at significantly greater distances and moved further in relation to what sound cues would normally imply about the velocity of approach. Absolute stimulus volume was not a significant predictor of response across object type. The responses occurred without the presence of visual cues, suggesting that an auditory cue alone and without visual confirmation can produce an appropriate response. Overall, this shows that this population of urban juncos has the ability to respond appropriately to novel anthropogenic sound cues. The question remains as to how universal such abilities are across species, different urban situations, and in natural habitats.